Understanding Public Discourse on History Textbooks in India - Ojha, Seema Shukla (Voices of Teachers and Teacher Educators, 2022)
The textbook is a major educational tool for the students in India occupying most of the educational space in schools. With a wide reach and potential to shape the minds of the younger generation, textbooks profoundly influence children on what they learn and how they see the world. Textbooks, are not just pedagogic tools but also a crucial disseminator of what people want to pass on to the next generation all over the world. As a result, textbook content is a hotly debated topic around the world. Among all disciplines, history textbooks invite most contestations and controversies. Some of the most virulent debates on textbooks throughout the world revolve around history textbooks. This is because, unlike mathematics, science, or geography, history deals with issues of nationality, culture, and ultimately, identity. It is history that, to a large extent, defines who we are, where we come from and where we might be going. This is possibly why, in a diverse country like ours, the issue of history textbooks becomes a hotbed of contestations and divergent interpretations. Various debates and controversies erupting regularly over historical distortions, writing and rewriting of history textbooks, attest to this. Therefore, textbook content is critical and has a direct effect on students’ educational progress. This paper looks at various such issues and concerns raised in letters by various stakeholders on history textbooks of NCERT from 2005 till 2020 and attempts to highlight public discourse on history textbooks in India and their implications for future history textbook writing.